Methotrexate inhibits proliferation but not proteoglycan synthesis or glycosaminoglycan hyperelongation in human vascular smooth muscle cells - Little, Peter J.; Getachew, Robel; Kamato, Danielle; Rostam, Muhamad Ashraf; Cohen, Neale; Chan, Vincent; Osman, Narin (OMICS International, 2015)
Objectives: Atherosclerosis is a disease process involving the early deposition of lipids in the vessel wall trapped by modified proteoglycans and subsequently a chronic inflammatory process leading to the clinical events. MTX has been chosen to study the potential efficacy of an anti inflammatory agent in preventing atherosclerosis and secondary cardiovascular disease in the cardiovascular inflammation reduction trial (CIRT). Methods: We have investigated cell proliferation and growth factor stimulated proteoglycan synthesis in vascular smooth muscle (VSMC) to assess some of the direct effects of MTX. Experiments were conducted in cultured human VSMC. Proliferation was assessed by the gold standard technique of cell counting and proteoglycan synthesis by 35S radiosulafate incorporation and size analysis by SDS PAGE. Key findings: MTX had a concentration-dependent inhibitory effect on serum stimulated VSMC proliferation with a maximum and total inhibitory effect at 10 μM. Thrombin, platelet-derived growth factor and transforming growth factor beta stimulated proteoglycan synthesis and increased the size of the biglycan molecules but MTX (10 μM) had no effect on any of these responses. Conclusions: The outcome of a trial with MTX will reflect the potential of targeting inflammation for the prevention of atherosclerosis and it remains an interesting proposition to evaluate the effects of a “proteoglycan inhibitor” on atherosclerosis.